The use of YouTube in children’s vocabulary acquisition: a case study of 3 and 5-year-old children in Medan - Anshary, Elvira Putri; Br.Perangin-angin, Alemina (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2024)
Acquisition of a second language can be obtained through the influence of the environment or activities carried out continuously. This study will describe how the effect of viewing on social media YouTube affects the acquisition of a second language for a-three-years old and five years old girl. This study aims to analyze the differences between children aged 3 and 5 years in the acquisition of English vocabulary which is influenced by the child's habit of watching English videos on YouTube. This research is using a qualitative descriptive method. The data collection technique in this research is an interview with children's parents, which is in the form of a conversation between the speaker and the interlocutor where the researcher will ask several questions about vocabulary obtained via YouTube by children aged 3 and 5 years. These habits have an influence on vocabulary acquisition because there are differences in the repetition process of children's viewing. The research found that 3-year-olds can learn many English words and say them naturally by repeating and forming habits. The vocabulary results spoken by the subjects in this study were nouns, verbs, adjectives, phrases and simple sentences. On the other hand, 5-year-olds don't do as well because they watch both English and Indonesian videos, dividing their attention and leading to a lack of understanding and practice.